(untitled) (Deutscher Suchtkongress, 2023)
Hintergrund und Fragestellung Eastern Europe and Central Asia has the fastest growing HIV epidemic in the world. According to the Joint United Nations Program on HIV/AIDS (UNAIDS) approximately 1.4 million people are living with HIV in the region. In 2021, about 160 000 people were newly infected with, which constitutes an increase of 48% increase since 2010 (UNAIDS, 2022). The dynamic of the epidemics in Central Asia, however, points to a number of risk factors that have enabled the spread of HIV in the region, including injecting drug use, sex work, and labor mobility between Russia and Central Asia. Initially, the HIV/AIDS epidemic in Central Asia has been mainly driven by injecting drug use. In recent years, however, the majority of infections are transmitted via sexual contact. Young people are among those most at risk. Against this background, it is of crucial important to get a clear picture of the level of knowledge on HIV/Aids among students. Methoden This comparative study is based on an online survey among social work students in Kyrgyzstan and Kazakhstan (n = 150). Ergebnisse The findings show that social work students have basic knowledge about HIV/Aids, but lack sufficient information on social work services for this target group. Particularly, students of social work are not sufficiently informed about the legal regulations, about guaranteed state services for people living with HIV/Aids (PLWH) and the specificies of working with people with HIV/Aids, including questions of confidentiality and the use of approaches such as motivational interviewing. The findings of the online survey also show that social work students mainly obtain information from internet resources and from social media. At the university, social work students receive only little information on HIV/Aids and on social work services for PLWH. Diskussion und Schlussfolgerung HIV/Aids is not sufficiently included in the social work curriculum in Kyrgyzstan and Kazakhstan. Offenlegung von Interessenskonflikten sowie Förderungen Ich und die Koautorinnen und Koautoren erklären, dass während der letzten 3 Jahre keine wirtschaftlichen Vorteile oder persönlichen Verbindungen bestanden, die die Arbeit zum eingereichten Abstract beeinflusst haben könnten. Erklärung zur Finanzierung: DAAD